The Relationship Between Basic Pattern Making and Pattern Drafting Skills and Student Learning Outcomes in the Women’s Fashion Making Course - Rizka Amalia; Irmayanti Irmayanti (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
In the context of vocational education, mastery of basic pattern-making and pattern drafting skills is one of the main competency outcomes that must be achieved by students in the Fashion Education Study Program, as it serves as a fundamental basis in the fashion production process. This study aims to examine the relationship between basic pattern-making and pattern drafting skills and students’ learning outcomes in the Women’s Garment Production course. This research employed a quantitative approach using an ex post facto correlational research design. The population of this study consisted of students of the Fashion Education Study Program, Department of Family Welfare Education, Faculty of Engineering, Semarang State University, class of 2024, who had completed the Clothing Pattern Construction and Women’s Fashion Production courses. A total of 91 students were involved as samples using a total sampling technique. Data were collected through documentation in the form of final grades from the Clothing Pattern Construction course as indicators of basic pattern-making and pattern drafting skills, and final grades from the Women’s Fashion Production course as indicators of students’ learning outcomes. Data analysis included descriptive analysis, normality testing, and Spearman Rank correlation analysis. The results showed a significance value of 0.000 (p < 0.05) with a correlation coefficient of 0.537, indicating a significant, strong, and positive relationship between basic pattern-making and pattern drafting skills and students’ learning outcomes in the Women’s Garment Production course. These findings indicate that mastery of pattern-making skills plays an important role in improving students’ learning achievement in Fashion Education.